Experimental Study on Electrical Properties of Steel-fibre Reinforced Concrete. (2016) - Fiala, Lukáš; Toman, Jan; Vodička, Jan; Ráček, Václav
Abstract: The electrical resistivity is an important parameter describing materials' ability to conduct electric current. Dry cementitious materials exhibit very high value of the electrical resistivity due to their insulating nature. Indeed, the electrical resistivity of an oven-dried concrete is about 10 9 Ω m. However, it can be significantly decreased by a sufficient amount of electrically conductive admixture. Such an enhancement is beneficial in self-sensing or self-heating concrete design, but it is not convenient in special cases such as design of concrete used for railroad ties production. In this case, mechanical properties (tensile strength) need to be improved without an accompanying decrease of the electrical resistivity. In this paper, reference concrete together with three types of steel-fibre reinforced concrete (0.5% vol., 1% vol., 2% vol.) were prepared and analyzed in terms of determination of electric properties. Experiments were carried out in both, DC and AC electric regime by means of precise DC multimeter and LCR meter measurements.